Case report: A case of piriformis pyomyositis and pyogenic sacroiliitis due to non-typhoidal Salmonella bacteremia in an immunocompetent healthy adult - Kanno, Atsuhiro; Suzuki, Kohei; Narai, Daiki; Aihara, Akinobu; Ito, Takehito; Ohara, Takahiro; Sumitomo, Kazuhiro; Furukawa, Katsutoshi (Frontiers in Medicine, 2024)
Non-typhoidal Salmonella (NTS) rarely causes bacteremia and subsequent focal infections as an extraintestinal complication, even in immunocompetent adults. A 25-year-old man was hospitalized for several days with difficulty moving due to fever, acute buttock pain, and shivering. He had no recent or current respiratory symptoms and no clear gastrointestinal symptoms. Physical examination revealed mild redness around the left buttock and difficulty raising the left lower extremity due to pain, in addition to which blood tests showed high levels of inflammatory markers. His clinical course and laboratory findings suggested sepsis, and magnetic resonance imaging revealed a high-intensity area in the left piriformis muscle on diffusion-weighted imaging; therefore, acute piriformis pyomyositis was strongly suggested. Cephazolin was started upon hospitalization; however, blood and stool cultures proved positive for NTS, and the antibiotics were changed to ceftriaxone. Follow-up MRI showed a signal in the left piriformis muscle and newly developed left pyogenic sacroiliitis. On the 25th hospital day, a colonoscopy was performed to identify the portal of entry for bacteremia, which revealed a longitudinal ulcer in the sigmoid colon in the healing process. His buttock pain gradually improved, and the antibiotics were switched to oral levofloxacin, which enabled him to continue treatment in an outpatient setting. Finally, the patient completed seven weeks of antimicrobial therapy and returned to daily life without leaving any residual disability. Invasive NTS infection due to bacteremia is rare among immunocompetent adults. Piriformis pyomyositis and subsequent pyogenic sacroiliitis should be added to the differential diagnosis of acute febrile buttock pain. In the case of NTS bacteremia, the entry site must be identified for source control. Additionally, the background of the host, especially in such an immunocompetent case, needs to be clarified; therefore, the patient should be closely examined.